The Strengths and Difficulties Questionnaire Predicts Concurrent Mental Health Difficulties in a Transdiagnostic Sample of Struggling Learners - Bryant, Annie; Guy, Jacalyn; , The CALM Team; Holmes, Joni; Astle, Duncan; Baker, Kate; Gathercole, Susan; Holmes, Joni; Kievit, Rogier; Manly, Tom; Bathelt, Joe; Bennett, Marc; et al. (Frontiers in Psychology, 2020)
Children and adolescents with developmental problems are at increased risk of experiencing mental health problems. The Strengths and Difficulties Questionnaire (SDQ) is widely used as a screener for detecting mental health difficulties in these populations, but its validity thus far has been restricted to groups of children with diagnosed disorders (e.g. ADHD). Transdiagnostic approaches, which focus on symptoms and soften or remove the boundaries between traditional categorical disorders, are increasingly adopted in research and practice. The aim of this study was to assess the potential of the SDQ to detect mental health problems in a transdiagnostic sample of children. The sample were referred by health and educational professionals for difficulties related to learning (N=389). Some had one diagnosis, others had multiple, but many had no diagnoses. Parent-rated SDQ scores were significantly positively correlated with parent ratings of mental health difficulties on the Revised Child Anxiety and Depression Scale (RCADS). Ratings on the SDQ Emotion subscale significantly predicted the likelihood of having clinical anxiety and depression scores. Ratings on the Hyperactivity subscale predicted anxiety levels. These findings suggest the SDQ could be a valuable screening tool for identifying mental health difficulties in children recognised as struggling, as it can be in typically developing children and those with specific diagnoses.